A new type of slumping-induced soft-sediment deformation structure: the envelope structure - Byun, Uk Hwan; van Loon, A.J. Tom; Kwon, Yi Kyun; Ko, Kyoungtae (Geologos, 2019)
The sediments of the Cretaceous Gyeokpori Formation in south-western South Korea accumulated in a lake in which mainly siliciclastic rocks were deposited, with some interbedded volcaniclastics. The nearby volcanic activity resulted in unstable lake margins inducing a dominance of gravity-flow deposits. The high sedimentation rate facilitated soft-sediment deformation on the sloping margin. The deposition of numerous gravity-flow deposits resulted in a vertically heterolithic stratification. The slumps are composed of different lithologies, which is expressed in different types of deformation due to the difference in cohesion between sandy and mussy layers within the slumps. Coarser-grained (cohesionless) slumps tend to show more chaotic deformation of their lamination or layering. The difference in slumping behaviour of the cohesive and non-cohesive examples is explained and modelled. A unique soft-sediment deformation structure is recognized. This structure has not been described before, and we call it ‘envelope structure’. It consists of a conglomerate mass that has become entirely embedded in fine-grained sediment because slope failure took place and the fine-grained material slumped down with the conglomerate ‘at its back’. The cohesive laminated mudstone formed locally slump folds that embedded the non-cohesive overlying conglomerate unit, possibly partly due to the bulldozing effect of the latter. This structure presumably can develop when the density contrast with the underlying and overlying deposits is exceptionally high. The envelope structure should be regarded as a special – and rare – type of a slumping-induced deformation structure.